Application of Innovative Technologies in the Process of Preparing Young Sprinters - Abdujabbarovich, Chariev Ulugbek (European Journal of Life Safety and Stability (2660-9630), 2022)
The article deals with the methodological approach to the use of complexes of special preparatory exercises, which allow to increase the efficiency of the training process, to achieve effective indicators of the special performance of young sprinters.